2019
DOI: 10.1186/s13048-019-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lymphocyte-to-monocyte ratio in ovarian cancer: a meta-analysis

Abstract: Introduction Prognostic biomarkers are highly needed to properly manage patients with cancer and improve their clinical courses. The relationship between lymphocyte-to-monocyte ratio (LMR) at diagnosis and ovarian cancer prognosis has been extensively studied, but little consensus has been reached regarding its utility as a biomarker of poor outcome. Thus, this study aimed to investigate the potential prognostic value of pretreatment LMR in such patients to shed light on this issue. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 28 publications
6
40
0
Order By: Relevance
“…In this study, we attempted to determine preoperative indicators to stage OC to help attain ODS, reduce surgical complications and economic burden, and better evaluate the prognosis of OC patients. Multivariate logistic regression analysis showed that LMR was signi cantly associated with stage of OC (Table 3): the lower the LMR, the higher the stage, and the worse the prognosis, which was consistent with the conclusion of previous research [10]. Our study also showed that serum CA125 was associated with stage of OC (Table 3); however, the speci city was lower than LMR (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we attempted to determine preoperative indicators to stage OC to help attain ODS, reduce surgical complications and economic burden, and better evaluate the prognosis of OC patients. Multivariate logistic regression analysis showed that LMR was signi cantly associated with stage of OC (Table 3): the lower the LMR, the higher the stage, and the worse the prognosis, which was consistent with the conclusion of previous research [10]. Our study also showed that serum CA125 was associated with stage of OC (Table 3); however, the speci city was lower than LMR (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we attempted to explore preoperative indicators to stage OC to help predict optimal debulking surgery, reduce surgical complications and economic burden, and better evaluate the prognosis of OC patients. Multivariate logistic regression analysis showed that LMR was significantly associated with stage of OC (Table 3 ): the lower the LMR, the higher the stage, and the worse the prognosis, which was consistent with the conclusion of previous research 17 . Our study also showed that serum CA125 was associated with stage of OC (Table 3 ); however, the specificity was lower than LMR.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, in recent years, many researchers have investigated the value of blood constituents in the systemic inflammatory response and reported that single elements of a complete blood sample may have clinical utility in the prediction of cancer outcome. Many of these indexes, such as the platelet-to-lymphocyte ratio, monocyte-to-lymphocyte ratio, and, in particular, the NLR are currently used as prognostic indexes [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%